Prospects for Obtaining Synthetic Fuel from Biomass and Other Household Waste - O.Z. Odilov; J.B Daliev (Genius Journals, 2022)
The article provides a variety of obtaining synthetic fuel from biological municipal waste. As well as increasing the role of various alcohols in internal combustion engines, dehydration methods for obtaining dimethyl ethers from methanol.
Keywords: Biomass; natural gas; synthetic diesel fuel; ethanol